Hubungan antara Kepemimpinan Transformasional Kepala Sekolah dan Profesionalitas Guru dengan Kepuasan Kerja Guru di Sekolah Dasar Negeri Kecamatan Cengkareng Kota Administrasi Jakarta Barat - Laila, Yuniarti Dewi (Universitas Muhammadiyah Prof. DR. HAMKA, 2015)
The reseach is aimed at finding and whether there is any correlation between Principal Transformational Leadership (X1) and Teacher Profesionalism (X2) withTeacher Work Satisfaction (Y). The methode applied in this reseach is a survey methode with correlation technique. This study uses 100 Elementary School Teacher in the Cengkareng District, West Jakarta, municipality which registered in the school year 2014/2015. Sample is randomly drawn into as many as using the technique random sampling proportional. Data for three variable is collected throught is three questionnaire instrument: (1) Principal Transformational Leadership Questionnare, (2) Teacher Profesionalism Questionnare, and (3) Teacher Work SatisfactionQuestionnare. The result show: (1) there is a positive correlation between Principal Transformational Leadership and the Teacher Work Satisfaction, indicated by correlation coeficient ry1 = 0,582 and simple linear regression aquation ^Y= 49,23 +0,550 X1 (2) there is a positive correlation between Teacher Profesionalism and the Teacher Work Satisfaction, indicated by correlation coeficient ry2 = 0,548 and simple linear regression equation ^Y = 56,03 + 0,470 X2 (3) there is a positive correlation between Principal ransformational Leadership and Teacher Profesionalism with the Teacher Work Satisfaction shown by correlation coeficient Ry12 = 0,692 and multiple regression equation ^Y= 23,115 +0,424 X1 + 0,340 X2 . Based on the result of hyphothesis, it can be concluded, the Principal Transformational Leadership andTeacher Profesionalism can be the higher the Teacher Work Satisfaction, independently as well as simultaneusly.